THE RELATIONSHIP BETWEEN EATING BEHAVIOR AND BODY IMAGE IN STUDENTS OF THE Batch OF 2022 AT STIKES MAHARANI MALANG - Eva Nurul Fadilah; Risna Yekti Mumpuni; Ratna Wulandari (PROFESSIONAL HEALTH JOURNAL, 2024)
Excessive concern about body image among women results in body shape dissatisfaction that will affect psychological well-being, and eating behavior becomes inadequate. The research design used a correlational design with a cross-sectional approach. The total sample consisted of 67 respondents. The sampling technique used was Proportionate Stratified Random Sampling. This study used an eating behavior scale questionnaire (Chairiah, 2008) and the MBSRQ-AS (Azminada, 2022) to assess body image. The results showed good eating behavior in students, which was 95.5%, followed by good body image with a total of 94%. The results of the analysis of the Spearman Rho test obtained a p value of 0.000. The result of the correlation value (r = 0.555) shows a positive and strong relationship between eating behavior and body image, which means that the better the eating behavior, the more positive the body image of female students of Batch 2022 STIKes Maharani Malang. A person with a negative body image will experience dissatisfaction with his body, which will lead to self-evaluation of the appearance of the body, which will result in changes in eating behavior.